Tournier's Theoretical Pretext Works Like a Charm - Lawrence R. Schehr (Studies in 20th & 21st Century Literature, 1988)
By playing on the expectations that a reader would have for a Bildungsroman, Tournier puts generic parameters and received ideas into question. In La Goutte d'or, he writes a text in which thematic considerations become so over-determined that they give way to a set of theoretical considerations about how the novel is constructed and perceived. Tournier does engage the reader in two "orthodox" theoretical perspectives on the nature of the text. The first involves the generation of meaning through the determination of a signified; the second involves the play of the signifier. But the largest portion of the theoretical perspectives of the novel is given over to the development of a phenomenological position of perception within the text. Tournier generates a structure of intentionality, signification, and meaning that he "develops" by means of the novel's fil conducteur, the photographic image. Tournier eventually refuses the status of image-making for the text and closes with a theoretical perspective that depends on the double valorization of writing: as the aesthetic dance of signifiers and as the seduction of the well-told tale.
Keywords: Bildungsroman; Tournier; La Goutte d& #x27; or; generic; over-determined; theoretical considerations; orthodox; generation of meaning; signified; signifier; phenomenological; perception; intentionality; signification; meaning; fil conducteur; photographic image; image-making